Analisis pengaruh perputaran kas, perputaran piutang, perputaran persediaan, perputaran modal kerja dan DPR terhadap profitabilitas (ROA) - Avonia Linang, Margaretha; Wahyu Setiyowati, Supami; Retna Sari, Ati (Jurnal Riset Pendidikan Ekonomi, 2025)
The purpose of this study was to examine the effect of operating capital turnover, cash turnover, accounts receivable turnover, inventory turnover, and DPR on profitability (ROA) of manufacturing businesses from 2020 to 2023. Secondary data in the form of annual financial reports of manufacturing businesses listed on the Indonesia Stock Exchange (IDX) at the specified time were used in this study. The method used to determine the sample size of this study was purposive sampling, which amounted to 41 companies. The data analysis method used in this research is Partial Least Squares-Structural Equation Modeling (PLS-SEM). SmartPLS software is used to test the relationship between the dependent variable, profitability (ROA), and the independent variables, cash turnover, accounts receivable turnover, inventory turnover, working capital turnover, and DPR. From the test results that have been carried out, the results obtained are that accounts receivable and inventory turnover have no effect on profitability, while cash turnover, working capital turnover, and DPR have an effect.